(untitled) (Journal of Sciences & Technology, 2021)
In astrophysical environment, allowed Gamow-Teller (GT) transitions and space phase factors play an important role in determination of transition rates and half-lives, particularly for β-decay in presupernova evolution of massive stars. The estimation of these half-lives in neutron rich nuclei is needed in astrophysics for the understanding of supernovae explosions and the processes of nucleosynthesis, principally the r-process, and in the experimental exploration of the nuclear landscape. Their determination in agreement with experimental results is a challenging problem for nuclear theorists. In this work, the total β-decay half-lives and rates of 134-136Sn nuclei at different temperatures are calculated using various interactions developed in the light of recently available information on experimental binding energies and low-lying spectra of Sn, Sb and Te isotopes in 132Sn mass region. The calculation has been realized using Oxbash code in the frame work of the nuclear shell model. With these interactions, one can observe that the effective half-lives increase and the total decay rates decrease with increasing temperature. A deviation of half-lives starts at around 0.2 MeV and satures above 10 MeV, but the half-lives limit values are slightly different for all interactions.